Case Study of Security Development in an Agile Environment: Building Identity Management for a Government Agency - Kalle Rindell; Sami Hyrynsalmi; Ville Leppänen (United States, 2022)
In contemporary software development projects and computing tasks, security concerns have an increasing effect, and sometimes even guide both the design and the project's processes. In certain environments, the demand for the security becomes the main driver of the development. In these cases, the development of the product requires special security arrangements for development and hosting, and specific security-oriented processes for governance. Compliance with these requirements using agile development methods may not only be a chance to improve the project efficiency, but can in some cases, such as in the case discussed in this paper, be an organizational requirement. This paper describes a case of building a secure identity management system and its management processes, in compliance with the Finnish government's VAHTI security instructions. The building project was to be implemented in accordance to the governmental security instructions, while following the service provider's own management framework. Project itself was managed with Scrum. The project's steering group required the use of Scrum, and this project may be viewed as a showcase of Scrum's suitability to multi-teamed, multi-site, security standard-compliant work. We also discuss the difficulties of fulfilling strict security regulations regarding both the development process and the end product in this project, and the difficulties utilizing Scrum to manage a multi-site project organization. Evaluation of the effects of the security work to project cost and efficiency is also presented. Finally, suggestions to enhance the Scrum method for security-related projects are made.
Proceedings of 11th International Conference on Availability, Reliability and Security (ARES)